Enhancing Language Learners’ Speaking Skills and Confidence with AI A Study of Adaptive Interactive Methods - Said Miftahul, Fahmi; Zahria, Amalina; Rizka, Marlisa Aini (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Artificial intelligence (AI) continues to redefine education by providing novel strategies to improve language learners’ speaking skills and boost their confidence. This study examines the efficacy of AI-powered adaptive interactive methods in fostering improved speaking fluency, accurate pronunciation, and learner self-assurance. Our research is grounded in a mixed-method approach, utilizing quantitative performance measures and qualitative learner feedback. The results underscore AI’s potential in personalizing learning experiences, reducing anxiety, and building sustained competence in spoken communication. This paper also discusses implementation challenges, ethical considerations, and pathways for future research on AI-assisted language learning.